5-Hydroxymethylfurfural Content in Selected Food Products - Mańkowska, Dorota; Majak, Iwona; Łącka, Agata; Słownianek, Marta; Bartos, Adrian; Leszczyńska, Joanna (Lodz University of Technology Press, 2015)
5-hydroxymethylfurfural (HMF) is a common component of heat treated, drying or stored for a long time food products. It is an intermediate product formed in the Maillard reaction as a result of thermal dehydration of reducing sugars (1-2). HMF is also formed during caramelisation while degradation of carbohydrates at high temperature (3). HMF is responsible for the sensory properties of food, especially for the pleasant flavor. Although it is relatively safe food component, there are reports regarding toxic, mutagenic and carcinogenic properties of HMF, and of 5-sulphoxymethylfurfural especially, an allylic sulfuric acid ester metabolite from HMF (4-6). The content of HMF in the various products vary within a wide range and depends on the food group type as well as the type of processing. In present work, the HMF content in different types of breakfast cereals, cookies and muesli as well as in several types of bakery products commercially available in Poland was determined. In addition, the influence of flavor and taste additives (honey, cocoa, dry fruits) as well as the type of cereals (gluten or gluten-free) on the HMF content in the tested products was examined.